2010
DOI: 10.1017/s0027763000009910
|View full text |Cite
|
Sign up to set email alerts
|

Hilbert-Samuel polynomials for the contravariant extension functor

Abstract: Abstract. Let (R, m) be a local ring and M and N finite R-modules. In this paper we give a formula for the degree of the polynomial giving the lengths of the modules Ext i R (M, N/m n N ). A number of corollaries are given and more general filtrations are also considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Remark 10. It should be noted that [5,Remark 5.6] claims that using [5, Proposition 5.5] one can show that if R is equidimensional and Conjecture 4 is true, then dim(Ω n (M )) is constant for n ≫ 0. However, [5,Proposition 5.5] requires the assumption that dim(R) 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Remark 10. It should be noted that [5,Remark 5.6] claims that using [5, Proposition 5.5] one can show that if R is equidimensional and Conjecture 4 is true, then dim(Ω n (M )) is constant for n ≫ 0. However, [5,Proposition 5.5] requires the assumption that dim(R) 2.…”
Section: Resultsmentioning
confidence: 99%
“…This question was also explored in the last section of [5]. In [5,Remark 5.2 (i)] it is noted that if R is unmixed and equidimensional, then (dim(Ω i (M ))) ∞ i=0 is constant for i ≫ 0.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the lengths of the R-modules Ext 1 R (M, R/m n R) are given by a polynomial ξ M,m (n) for all n large enough (see [12], [16]). In [4], the authors give an exact formula for the degree of this polynomial; in particular when M has constant rank on the punctured spectrum, the degree is dim R − 1.…”
Section: Constructing Big Indecomposable Modules 2183mentioning
confidence: 99%
“…The present paper is motivated by Kodiyalam's work [6], the papers by Theodorescu [11], by Katz and Theodorescu [8], [9] and the paper [3]. In these papers it was shown that for finitely generated R-modules M and N over a Noetherian (local) ring R, and for an ideal I ⊂ R such that the length of Tor In these papers bounds are given for the degree of these polynomials.…”
Section: Introductionmentioning
confidence: 99%